Envelope glycoprotein domain III (EDIII): potential as bio-receptor probe for specific detection of different serotypes of dengue antibodies - Tan, Shi Hui (2025)
Dengue fever has been a global threatening disease, affecting approximately 40% of the world’s population (3.6 billion) residing in dengue-endemic areas across more than 100 countries within the World Health Organisation (WHO) regions. Dengue fever is caused by dengue virus (DENV) which constitutes four distinct antigenic serotypes (DENV1, DENV2, DENV3 and DENV4). Infection with one serotype of DENV is thought to produce long-term immunity against that particular serotype but only short-term cross-immunity against the other serotypes. Sequential infections with different DENV serotypes lead to cross-reactive but also serotype-specific neutralizing antibody responses. This potentially results in life-threatening complications, i.e. antibody dependent enhancement (ADE). ADE is a phenomenon in which the antibodies produced during a previous immune response recognize and bind to the pathogen, but they are unable to prevent the subsequent infection. Instead, they facilitate viral entry into cells, leading to increased viral replication and more severe disease outcomes. Therefore, there is a pressing need to develop a cheap, rapid, and highly sensitive point-of-care diagnostic tool for early serotype-specific DENV detection, as early detection and prompt medical treatment can reduce the mortality rates associated with dengue fever. However, the current diagnostic landscape lacks sufficiently sensitive, specific, and rapid tools capable of differentiating DENV infections based on serotypes.